Effect of Acidic Challenge Preceded by Food Consumption on Enamel Erosion - Honório, Heitor Marques (Dental Investigations Society, 2010)
OBJECTIVES: This in vitro study aimed to evaluate the effect of food consumption followed by acidic challenge on enamel erosion. METHODS: Seventy-five enamel blocks obtained from bovine teeth were divided randomly into five groups (n=15 per group): GI – erosion with previous immersion in milk; GII – erosion with previous immersion in cheese extract; GIII – erosion with previous immersion in liver extract; GIV – erosion with previous immersion in broccoli extract; and GV – erosive effect of cola drink (control). Over 24 h, the slabs were submitted to 3 pH-cycles, each consisting of immersion in the studied food (GI to GIV) for 5 min followed by immersion in a cola drink for 5 min, and subsequently, the slabs were stored in artificial saliva (110 min). At the end of the pH-cycles, the slabs were stored in artificial saliva for 18 h. Enamel alterations were assessed by profilometry (μm). Data were tested using ANOVA and Scott-Knott’s tests (P<.05). RESULTS: Mean erosion depths for enamel (μm) were 0.46 in GI, 0.55 in GII, 0.64 in GIII, 0.54 in GIV, and 1.18 in GVI. Enamel loss by acidic challenge alone (GV) was significantly higher than when the acidic challenges were preceded by food extract immersion. CONCLUSIONS: The data suggest that all studied foods could minimize the erosive effect on enamel.